Outdoor propagation prediction for WiMAX(802.16a) signals - 241358 Shivakumar Thayanithy (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2007